Broadband Ultra-high Frequency Sensor for Multi-condition Partial Discharge Detection in High-voltage Equipment - Faizol, Zulbirri; Zubir, Farid; Yahya, Salah I.; Ahmad, Mohd H.; Saman, Norhafezaidi M.; Ayop, Osman; Vallappil, Arshad K.; Abd Aziz, Mohamad Z. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
Partial discharge (PD) is a localized electrical phenomenon occurring within degraded insulation of high-voltage (HV) equipment, where its discharge mechanisms and radiated electromagnetic characteristics vary significantly across air, oil, and gas-insulated systems. Undetected PD can gradually damage insulation and eventually lead to equipment failure and power outages. Therefore, researchers are urged to develop reliable detection methods that are effective across different insulation media to ensure the safe operation of power systems. In this study, ultra-high frequency electromagnetic signals generated from PD activity are analyzed using an external log-periodic dipole array (LPDA) antenna. This research focuses on broadband sensing and considers the PD activity in various insulation materials, including air, oil, and gas. Moreover, lumped inductors are added to achieve a more compact antenna design without compromising the performance. The proposed LPDA antenna is fabricated on an FR-4 substrate and evaluated using a vector network analyzer. As a result, a reflection coefficient below −10 dB from 0.4 GHz to 2 GHz with a directional gain of 4–6 dBi is obtained, which satisfies the IEC 62478 standard. The results demonstrated that the proposed miniaturized LPDA antenna is effective for PD detection in different insulation environments.